The V1-V3 region of a brain-derived HIV-1 envelope glycoprotein determines macrophage tropism, low CD4 dependence, increased fusogenicity and altered sensitivity to entry inhibitors - Rossi, Fiorella (BioMed Central, 2008)
BACKGROUND: HIV-1 infects macrophages and microglia in the brain and can cause neurological disorders in infected patients. We and others have shown that brain-derived envelope glycoproteins (Env) have lower CD4 dependence and higher avidity for CD4 than those from peripheral isolates, and we have also observed increased fusogenicity and reduced sensitivity to the fusion inhibitor T-1249. Due to the genetic differences between brain and spleen env from one individual throughout gp120 and in gp41's heptad repeat 2 (HR2), we investigated the viral determinants for the phenotypic differences by performing functional studies with chimeric and mutant Env. RESULTS: Chimeric Env showed that the V1/V2-C2-V3 region in brain's gp120 determines the low CD4 dependence and high avidity for CD4, as well as macrophage tropism and reduced sensitivity to the small molecule BMS-378806. Changes in brain gp41's HR2 region did not contribute to the increased fusogenicity or to the reduced sensitivity to T-1249, since a T-1249-based peptide containing residues found in brain's but not in spleen's HR2 had similar potency than T-1249 and interacted similarly with an immobilized heptad repeat 1-derived peptide in surface plasmon resonance analysis. However, the increased fusogenicity and reduced T-1249 sensitivity of brain and certain chimeric Env mostly correlated with the low CD4 dependence and high avidity for CD4 determined by brain's V1-V3 region. Remarkably, most but not all of these low CD4-dependent, macrophage tropic envelopes glycoproteins also had increased sensitivity to the novel allosteric entry inhibitor HNG-105. The gp120's C2 region asparagine 283 (N283) has been previously associated with macrophage tropism, brain infection, lower CD4 dependence and higher CD4 affinity. Therefore, we introduced the N283T mutation into an env clone from a brain-derived isolate and into a brain tissue-derived env clone, and the T283N change into a spleen-derived env from the same individual; however, we found that their phenotypes were not affected. CONCLUSION: We have identified that the V1-V3 region of a brain-derived envelope glycoprotein seems to play a crucial role in determining not only the low CD4 dependence and increased macrophage tropism, but also the augmented fusogenicity and reduced sensitivity to T-1249 and BMS-378806. By contrast, increased sensitivity to HNG-105 mostly correlated with low CD4 dependence and macrophage tropism but was not determined by the presence of the brain's V1-V3 region, confirming that viral determinants of phenotypic changes in brain-derived envelope glycoproteins are likely complex and context-dependent.